Breakthrough candidemia after the introduction of broad spectrum antifungal agents: A 5-year retrospective study. (9th October 2017) - Breda, Giovanni L; Tuon, Felipe F; Meis, Jacques F; Herkert, Patricia F; Hagen, Ferry; de Oliveira, Letícia Z; Dias, Viviane de Carvalho; da Cunha, Clóvis Arns; Queiroz-Telles, Flávio
Abstract: Candidemia is the main invasive fungal disease among hospitalized patients. Several breakthrough candidemia (BrC) cases have been reported, but few studies evaluate the epidemiology, risk factors, molecular characterization, antifungal susceptibility profile and outcome of those patients, especially in developing countries and including patients using broad spectrum antifungals. We conducted a retrospective study from 2011 to 2016, including patients aged 12 years or older with candidemia. Epidemiological characteristics and risk factors for candidemia were evaluated and compared with patients with BrC using univariate and multivariate analysis. Sequential Candida isolates from BrC were identified by internal transcribed spacer sequencing, genotyped with amplified fragment length polymorphism fingerprinting (AFLP), and tested for antifungal susceptibility. From 148 candidemia episodes, 27 breakthrough episodes (18%) were identified, with neutropenia and mucositis being independent risk factors for BrC. Candida non- albicans was more frequent in the BrC group ( P < .001). AFLP showed high correlation with conventional methods of identification among breakthrough isolates and a high genetic similarity among isolates from the same patient was observed. C. albicans was the most susceptible species with low MIC values for all antifungal agents tested. In contrast, we found isolates of C. glabrata, C. parapsilosis and C. tropicalis resistant to triazoles and echinocandins. In conclusion, BrC occurred mainly in severely immunosuppressed patients, with neutropenia and mucositis. Mortality did not differ between the groups. Candida non- albicans species were more recovered from BrC, with C. albicans being the most susceptible to antifungals.